DISTRIBUTION TARGET STRENGTH IN WATERS BENGKALIS DEMERSAL FISH PROVINCE RIAU - Dedi Setiadi; Arthur Brown; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study uses data that has been taken in the period from October 31stuntil 7 November 2013 Bengkalis Bodies housed in Riau Province . This Methodis the method of acoustic survey and measurement of environmental parameters at5 stations that has been set. Distribution of value TS dernersal fish are in the range-70.00 dB to 30.00 dB. The fish demersal dominate in Bengkalis waters are indepth strata 40-50 meters and in the strength of the target range -70.00 dB to -30.00 dB with the highest number of targets on the 2nd leg of the total target of 11027 targets. Variations in the distribution of the value of TS mengindeksikan thatthe fish were detected including inshore fish schooling . Bengkalis depthrelatively shallow waters led to changes in temperature and salinity distribution ofvalues in each station is not significant. Distribution of temperature and salinityvalues Bengkalis waters tend to be uniform with an average temperature of 30.16° C and an average salinity of 26.2 ppt.Keywords : Distribution, acoustic, target strength.